Preparation method of ultra-high molecular weight propenyl elastomer
By leveraging the synergistic catalytic effect of quinolineamine-based binuclear metal hafnium catalysts, the problem of synthesizing ultra-high molecular weight atactic polypropylene has been solved, enabling the preparation of propylene-based elastomers with tunable molecular weight and stereostructure, suitable for highly flexible materials.
Patent Information
- Application Number
- CN202411752301.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing technologies make it difficult to efficiently synthesize ultra-high molecular weight atactic polypropylene, which limits its application in the field of special materials.
A quinolineamine-based binuclear metal hafnium catalyst was used to conduct homopolymerization and copolymerization of propylene through the synergistic catalytic effect of the binuclear metals, in conjunction with a co-catalyst, thereby controlling the molecular weight and stereostructure of the polymer.
Ultra-high molecular weight propylene-based elastomers with molecular weights of 50–500 × 10⁴ g/mol and isotacticity of 10–50% were successfully prepared. They possess excellent mechanical properties and tunable glass transition temperatures, making them suitable for highly flexible materials.
Smart Images

Figure BDA0005165299490000021 
Figure FDA0005165299480000011 
Figure HDA0005165299500000011
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an ultra-high molecular weight propylene-based elastomer with adjustable regularity through the synergistic effect of a binuclear metal catalyst. Background Art
[0002] The physical form and properties of polypropylene are mainly determined by the three-dimensional structure and molecular weight of its macromolecular chain. Both isotactic polypropylene (iPP) and syndiotactic polypropylene (sPP) are crystalline polymers with plastic properties. Atactic polypropylene (aPP) can be in the form of a mucus (molecular weight less than 10 3 ), a soft solid with a sticky texture (molecular weight about 10 4 ) and elastic solids (molecular weight greater than 10 5 ) and other forms. Random polypropylene with different molecular weights has great differences in performance and has different uses. It is precisely because of the increase in the use of aPP that the demand continues to increase, making direct synthesis necessary.
[0003] Ultra-high molecular weight random polypropylene (UHWMaPP) is a special type of elastomer with a molecular weight of millions and a linear structure. It has the characteristics of low hardness and high elongation. By adjusting the isotactic content of polypropylene between 90% and 10%, the performance of the resin material can be adjusted from high rigidity to high flexibility. Ultra-high molecular weight random polypropylene (UHWMaPP) is expected to be used in some special material fields because it can overcome the disadvantage of low strength of medium molecular weight random polypropylene. However, ultra-high molecular weight random polypropylene (UHWMaPP) is difficult to synthesize, and only a molecular weight of several hundred thousand can be obtained under normal polymerization conditions. There are still challenges in the preparation of ultra-high molecular weight random polypropylene (UHWMaPP).
[0004] To this end, patent CN1124740A discloses a catalyst prepared by reacting a magnesium chloride and silicon dioxide composite dual component as a carrier with TiCl4. The catalyst uses triethylaluminum as a cocatalyst to carry out propylene polymerization reaction, and can obtain random polypropylene with an isotacticity of 20% to 40%, but still has a crystallinity of 5% to 30%. CN1262283A discloses a magnesium halide reacting with a monohydric alcohol, and then adding clay 1 to 10 times the magnesium halide, stirring the reaction to prepare random polypropylene with an isotacticity of 25% to 40%. However, the polypropylene prepared by this catalyst is not completely random, but has a certain degree of crystallinity, and can only be partially soluble in ether or hexane solution, and the molecular weight of the polypropylene is medium, which is 2.35 to 21.2×10 4g / mol, and the distribution is wide between 7 and 20. Nomura et al. synthesized a monocyclopentadienyl-ketoamine metallocene catalyst to synthesize random polypropylene, but the catalyst performed poorly in high temperature resistance and preparation of ultra-high molecular weight polymers. The optimal polymerization activity temperature was 40 °C for the preparation of high molecular weight polymers of 62 to 125 × 10 4 g / mol (Polymers 2024,16,512). Rieger et al. synthesized ethylene-bridged asymmetric zirconium metal catalysts to synthesize polypropylene with different stereo defects, and concluded that with the increase of molecular weight, mechanical properties and elastic properties also gradually improved (J.Am.Chem.Soc.1999,121,4348; Macromolecules 2002,35,5742). O'Hare et al. prepared methylaluminoxane-supported phenoxy-semi-metallocene titanium catalysts to synthesize ultra-high molecular weight polypropylene with a molecular weight of about 2 million. Despite these advances, examples of highly active synthesis of ultra-high molecular weight propylene-based elastomers are still limited (Polym.Chem.2022,13,5597).
[0005] The present invention provides a method for preparing an ultra-high molecular weight propylene-based elastomer, which uses a quinoline amine binuclear metal hafnium catalyst to significantly increase the molecular weight of the propylene-based elastomer through the binuclear metal synergistic catalytic effect. The molecular weight of the propylene-based elastomer obtained by the present invention is 50 to 500×10 4 g / mol, molecular weight distribution of 1.1-4.0, isotacticity (based on the percentage of pentads [mmmm] of isotactic sequence of propylene units in propylene molecular chains) of 10-50%, glass transition temperature of -50-0°C, tensile strength of 0.1-15MPa, elongation at break of 100-3000%, and excellent mechanical properties. Therefore, the present invention is original and innovative, and provides a new direction for the development of the field of polyolefin materials. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing an ultra-high molecular weight propylene-based elastomer with controllable regularity through a binuclear metal synergistic catalytic effect.
[0007] The method for preparing an ultra-high molecular weight propylene-based elastomer of the present invention is characterized in that the ultra-high molecular weight propylene-based elastomer is prepared by homopolymerization of propylene, copolymerization of propylene and ethylene, and copolymerization of propylene and α-olefin;
[0008] The method for preparing the ultra-high molecular weight propylene-based elastomer of the present invention is characterized in that the catalyst used is a quinolineamino binuclear metal hafnium catalyst, the structure of which is shown in formula (I):
[0009]
[0010] In the above invention, the α-olefin is one or more of 1-butene, 1-hexene, 1-octene and 1-decene.
[0011] In the above invention, the quinoline amine-based binuclear metal hafnium catalyst needs to be coordinated with a co-catalyst for catalysis, and the co-catalyst is one or more of tripentafluorophenyl boron, triphenylcarbonium tetrakis(pentafluorophenyl)borate, aluminoxane, alkyl aluminum and alkyl aluminum chloride. The aluminoxane is methylaluminoxane, ethylaluminoxane or isobutylaluminoxane; the alkyl aluminum is trimethylaluminum, triethylaluminum, triisobutylaluminum or tri-n-hexylaluminum; the alkyl aluminum chloride is diethylaluminum monochloride, diethylaluminum sesquichloride or ethylaluminum dichloride.
[0012] The catalyst in the present invention catalyzes propylene homopolymerization, propylene and ethylene copolymerization, and propylene and α-olefin copolymerization. The polymerization temperature is 0-180°C, the polymerization pressure is 0.1-2MPa, the molar ratio of the catalyst to the co-catalyst is 1:(1-5000), the reaction time is 0.1-24h, and the solvent used for the polymerization is one or more of n-hexane, n-heptane, n-pentane, and toluene.
[0013] The present invention provides a method for preparing an ultra-high molecular weight propylene-based elastomer, which uses a quinoline amine binuclear metal hafnium catalyst to increase the molecular weight of the polymer through the binuclear metal synergistic catalytic effect. The molecular weight of the propylene-based elastomer obtained by the present invention is 50 to 500×10 4 g / mol, molecular weight distribution of 1.1-4.0, isotacticity (based on the percentage of pentads [mmmm] of isotactic sequence of propylene units in propylene molecular chains) of 10-50%, glass transition temperature of -50-0°C, tensile strength of 0.1-15MPa, elongation at break of 100-3000%, and excellent mechanical properties. Therefore, the present invention is original and innovative, and provides a new direction for the development of the field of polyolefin materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Ultra-high molecular weight of 3290 kg·mol -1 GPC spectrum of ultra-high molecular weight random polypropylene elastomer.
[0015] Figure 2 Ultra-high molecular weight of 4960 kg·mol -1 GPC spectrum of ultra-high molecular weight random polypropylene elastomer.
[0016] Figure 3 This is the NMR carbon spectrum of an ultra-high molecular weight random polypropylene elastomer with a stereoregularity of 6.8mmmm%.
[0017] Figure 4This is the NMR carbon spectrum of an ultra-high molecular weight random polypropylene elastomer with a stereoregularity of 15.4mmmm%.
[0018] Figure 5 This is a stress-strain tensile curve of an ultra-high molecular weight random polypropylene elastomer with an elongation at break of 1050%.
[0019] Figure 6 This is a stress-strain tensile curve of an ultra-high molecular weight random polypropylene elastomer with an elongation at break of 1400%.
[0020] Figure 7 This is a stress-strain tensile curve of a propylene-based elastomer with an elongation at break of 680%.
[0021] Figure 8 This is the stretching cycle curve of the elastic recovery experiment of propylene-based elastomer.
[0022] Fig. 9 This is the DSC curve of the glass transition temperature of ultra-high molecular weight random polypropylene -8.5°C.
[0023] Fig.10 This is the DSC curve of the glass transition temperature of the ultra-high molecular weight propylene-based elastomer -16°C.
[0024] Fig.11 The X-ray diffraction pattern of WAXD of ultra-high molecular weight atactic polypropylene is an amorphous polymer. DETAILED DESCRIPTION
[0025] The technical scheme of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the present invention is further illustrated by the embodiments, but the present invention is not limited thereto. The embodiments of the present invention can enable those skilled in the art to understand the present invention more comprehensively.
[0026] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. The corresponding synthesis method of the quinolineamino binuclear metal hafnium catalyst of the present invention is given in Example 1.
[0027] Example 1. Preparation of Quinoline Amino Binuclear Metal Hafnium Catalyst (Hf1)
[0028] Weigh 1,8-diaminoanthracene (0.416 g / 2 mmol) and 2-quinolinealdehyde (0.69 g / 4.4 mmol) into a round-bottom flask, add 20 mL of anhydrous ethanol, add 2 mg of p-toluenesulfonic acid as a catalyst, react at room temperature for 6 hours, and filter the obtained yellow suspension. Rinse with a small amount of icy ethanol to obtain 0.67 g of yellow-green ligand powder L1 with a yield of 82%. 1H NMR (400MHz, CDCl3): δ9.57(s,1H),8.98(s,2H),8.60(d,J=8.5Hz,2H),8.50(s,1H),8.20(d,J=8.4Hz,2H),8.16(d,J=8.5Hz,2H),7.99(d, J=8.1Hz,2H),7.91(d,J=8.2Hz,2H),7.82–7.78(m,2H),7.58–7.50(t,J=8.1Hz,J=8.2Hz,2H),7.56–7.52(m,2H),7.24(d,J=7.0Hz,2H)ppm. 13 CNMR (100MHz, CDCl3): δ160.98,155.36,148.71,148.23,136.55,132.65,130.16,130.06, 129.07,127.97,127.86,127.78,127.12,126.06,119.74,119.03,111.71ppm.Anal.Calcd for C 34 H 22 N4:C,83.93;H,4.56;N,11.51.Found:C,83.94;H,4.63;N,11.43.HRMS Calcd.for[M+H + ]487.5860,Found:487.5862.
[0029] Weigh hafnium tetrachloride (0.352g, 1.1mmol), add 10mL of anhydrous toluene, slowly add 1.6mL / 4.8mmol of methylmagnesium bromide solution (3M) at -40℃ (acetonitrile-liquid nitrogen cold bath), and stir for 2 hours. Then add ligand L1 (0.259g / 0.5mmol), react at -40℃ in the dark for 2 hours, and continue to react at room temperature for 5 hours. After the reaction, remove the solvent, extract with toluene, and filter to obtain 0.33g of product (Hf1) with a yield of 69%. 1H NMR (400MHz, C6D6): δ9.57 (s, 1H), 8.98 (s, 2H), 8.60 (d, J = 8.5Hz, 2H), 8.50 (s, 1H),8.20(d,J=8.4Hz,2H),8.16(d,J=8.5Hz,2H),7.99(d,J=8.1Hz,2H),7.91( d,J=8.2Hz,2H),7.82–7.78(m,2H),7.58–7.50(t,J=8.1Hz,J=8.2Hz,2H),7.56 –7.52(m,2H),4.9(q,2H),1.56(d,J=8.4Hz,6H),0.88(s,9H),0.80(s,9H)ppm. 13 C NMR (100MHz, CDCl3): δ160.98,155.36,148.71,148.23,136.55,132.65,130.16,130.06,129.07,127.9 7,127.86,127.78,127.12,126.06,119.74,119.03,111.71,56.49,56.43,19.51,17.22ppm.Anal.Calcd for C 42 H 46 Hf2N4:C,52.34;H,4.81;N,5.81.Found:C,52.40;H,4.76;N,5.80.
[0030] Example 2: Propylene Homopolymerization
[0031] The polymerization reaction was carried out on a 350mL homogeneous solution polymerization evaluation device. First, a 350mL glass reactor equipped with a magnet was dried continuously at 80°C for 6 hours, evacuated while hot and replaced with N2 three times for polymerization reaction. 2μmol catalyst, 2.2μmol triphenyl carbon tetrakis (pentafluorophenyl) borate and 50μmol methylaluminoxane were added. Al / Hf=100, B / Hf=1.2. The glass reactor was connected to the polymerization pipeline, and when the temperature rose to 80°C, 50mL toluene was added thereto. During the polymerization process, propylene gas was continuously introduced to ensure that the reaction pressure was 5atm, and the reaction was stirred vigorously for 5min. The reaction solution was neutralized with 5% hydrochloric acid-acidified ethanol solution to obtain a polymer precipitate, which was washed several times with ethanol and water, vacuum dried to constant weight, and weighed. The polymerization activity was 4.6×10 6 g·mol - 1 h -1 Polymer Mw = 3250 kg·mol -1 , Mw / Mn=2.1, T g=-4℃, mmmm%=9.8%, tensile stress: 4.8MPa, elongation at break 1400%.
[0032] Example 3: Propylene Homopolymerization
[0033] The polymerization process and reaction conditions were the same as in Example 2, and the polymerization temperature was 30°C. The polymerization activity was 4.96×10 6 g·mol -1 h -1 , polymer Mw = 5250 kg·mol -1 , Mw / Mn=2.1, T g =-3℃, mmmm%=18.8%, tensile stress: 6.4MPa, elongation at break 2230%.
[0034] Example 4: Propylene Homopolymerization
[0035] The polymerization reaction was carried out on a 1L homogeneous solution evaluation device. First, a 100mL steel reactor equipped with a magnet was used for the polymerization reaction. 50mL of toluene was injected with a syringe, the contents of the reactor were heated to 120°C, and the reactor was saturated with 1MPa propylene. 2μmol of catalyst, 50μmol of methylaluminoxane, and 2.2μmol of triphenyl carbon tetrakis (pentafluorophenyl) borate were added to the glove box, dissolved in toluene, and transferred to the catalyst storage tube through a syringe, and nitrogen (over 1MPa) was pressed into the reactor. During the polymerization process, ethylene gas was continuously introduced to ensure that the reaction pressure was 1MPa. After reaching the set reaction time of 5min, 2mL of ethanol was pressed into the reactor under nitrogen (over 1MPa), the reactor was cooled and vented, and the contents of the reactor were poured into a large amount of ethanol. The polymer precipitated and filtered to obtain the polymer, which was washed with a small amount of ethanol and finally vacuum dried overnight and weighed. The polymerization activity was 7.6×10 6 g·mol -1 h -1 , polymer Mw = 4230 kg·mol -1 , Mw / Mn=2.4, T g =-5℃, mmmm%=12.5%, tensile stress: 5.8MPa, elongation at break 1760%.
[0036] Example 5: Propylene Homopolymerization
[0037] The polymerization process and reaction conditions were the same as in Example 4, and the polymerization temperature was 160°C. The polymerization activity was 3.8×10 6 g·mol -1 h -1 , polymer Mw = 1150 kg·mol -1, mmmm%=6.8%, Mw / Mn=2.4, tensile stress: 1.5MPa, elongation at break 830%.
[0038] Example 6: Propylene Homopolymerization
[0039] The polymerization process and reaction conditions were the same as in Example 4, except that the cocatalyst was changed to 2.2 μmol trispentafluorophenyl boron and 100 μmol methylaluminoxane. The polymerization activity was 9605 kg·mol -1 h -1 , polymer Mw = 830 kg·mol -1 , Mw / Mn=2.3, T g =-10℃, mmmm%=13%, tensile stress: 2.5MPa, elongation at break 540%.
[0040] Example 7: Propylene Homopolymerization
[0041] The polymerization process and reaction conditions were the same as in Example 4, except that the polymerization time was changed to 10 min. The polymerization activity was 5.8×10 6 g·mol -1 h -1 , polymer Mw = 4870 kg·mol -1 , Mw / Mn=2.4, T g =-4℃, mmmm%=13%, tensile stress: 6.5MPa, elongation at break 2440%.
[0042] Example 8: Propylene Homopolymerization
[0043] The polymerization process and reaction conditions were the same as in Example 4, except that the polymerization time was changed to 20 min. The polymerization activity was 5.3×10 6 g·mol -1 h -1 , polymer Mw = 5230 kg·mol -1 , Mw / Mn=2.5, T g =-3℃, mmmm%=12.2%, tensile stress: 7.5MPa, elongation at break 2670%.
[0044] Example 9: Propylene Homopolymerization
[0045] The polymerization process and reaction conditions were the same as in Example 4, except that the polymerization time was changed to 40 min. The polymerization activity was 3.2×10 6 g·mol -1 h -1 , polymer Mw = 5650 kg·mol -1 , Mw / Mn=2.4, T g=-2℃, mmmm%=13.2%, tensile stress: 8.2MPa, elongation at break 2440%.
[0046] Example 10: Propylene Homopolymerization
[0047] The polymerization process and reaction conditions were the same as in Example 44, except that the polymerization time was changed to 60 min. The polymerization activity was 8.7×10 5 g·mol -1 h -1 , polymer Mw = 5950 kg·mol -1 , Mw / Mn=2.4, T g =-2℃, mmmm%=10.5%, tensile stress: 8.5MPa, elongation at break 2320%.
[0048] Example 11: Copolymerization of propylene and octene
[0049] A 350mL glass reactor equipped with a magnet was used for the polymerization reaction. 2μmol of catalyst C3, 2.2μmol of triphenyl carbon tetrakis (pentafluorophenyl) borate and 100μmol of methylaluminoxane were weighed in a glove box. Then the glass reactor was connected to the polymerization pipeline, and when the temperature rose to 120°C, 26.6mL of toluene and 23.4mL of 1-octene were added thereto. During the polymerization process, propylene gas was continuously introduced to ensure that the reaction pressure was 5atm. After reacting for 5 minutes, 30mL of ethanol was added to the reactor under a nitrogen atmosphere. After cooling, the reaction solution was poured into a large amount of ethanol for sedimentation, and the final polymer was obtained by filtration and drying. Polymerization activity: 35300kg·mol -1 (Hf) h -1 , polymer Mw = 4320 kg·mol -1 , Mw / Mn=2.2, T g =-39°C, tensile stress: 0.8MPa, elongation at break>2000%, 1-octene content in the copolymer 28.4mol%.
[0050] Example 12: Copolymerization of propylene and octene
[0051] The polymerization process and reaction conditions were the same as in Example 11, with 34.4 mL of toluene and 15.6 mL of 1-octene. Polymerization activity: 39400 kg·mol -1 (Hf) h -1 .Polymer Mw = 4150 kg·mol -1 , Mw / Mn=2.3, T g =-28℃, tensile stress: 1.1MPa, elongation at break>2000%, 1-octene content in the copolymer 21.8mol%.
[0052] Example 13: Copolymerization of propylene and octene
[0053] The polymerization process and reaction conditions were the same as in Example 11, except that 42.2 mL of toluene and 7.8 mL of 1-octene were used. Polymerization activity: 24900 kg·mol -1 (Hf) h -1 .Polymer Mw = 437 kg·mol -1 , Mw / Mn=2.2, T g =-16℃, tensile stress: 1.5MPa, elongation at break>2000%, 1-octene content in the copolymer 13.5mol%.
[0054] Example 14: Copolymerization of propylene and octene
[0055] A 100mL steel reactor equipped with a magnet was used for the polymerization reaction. A mixture of 26.6mL toluene and 23.4mL 1-octene (50mL in total) was injected with a syringe, the contents of the reactor were heated to 120°C, and the reactor was saturated with 1Mpa propylene. 2μmol of catalyst, 100μmol of methylaluminoxane, and 2.2μmol of triphenyl carbon tetrakis (pentafluorophenyl) borate were added to the glove box, dissolved in toluene and transferred to the catalyst storage tube through a syringe, and then pressed into the reactor with nitrogen (over 1MPa). During the polymerization process, the reaction pressure was ensured to be 1MPa by continuously introducing propylene gas. After reaching the set reaction time of 5min, 2mL of ethanol was pressed into the reactor under nitrogen (over 1MPa), the reactor was cooled and vented, and the contents of the reactor were poured into a large amount of ethanol. The polymer precipitated and filtered to obtain the polymer, which was washed with a small amount of ethanol and finally vacuum dried overnight and weighed. Polymerization activity: 35300kg·mol -1 (Hf) h -1 , polymer Mw = 3920 kg·mol -1 , Mw / Mn=2.1, T g =-16℃, tensile stress: 2.6MPa, elongation at break>2000%, 1-octene content in the copolymer is 15.6mol%.
[0056] Example 15: Copolymerization of propylene and octene
[0057] The polymerization process and reaction conditions were the same as in Example 14, and the polymerization pressure was 2 MPa. Polymerization activity: 44300 kg·mol -1 (Hf) h -1 .Polymer Mw = 5410 kg·mol -1 , Mw / Mn=2.1, T g=-12℃, tensile stress: 2.75MPa, elongation at break>2000%, 1-octene content in the copolymer 8.5mol%.
[0058] Example 16: Copolymerization of propylene and octene
[0059] The polymerization process and reaction conditions were the same as in Example 14, and the polymerization pressure was 3 MPa. Polymerization activity: 55600 kg·mol -1 (Hf) h -1 .Polymer Mw = 5680 kg·mol -1 , Mw / Mn=2.0, T g =-10℃, tensile stress: 4.5MPa, elongation at break>2000%, 1-octene content in the copolymer 6.8mol%.
[0060] Example 17: Copolymerization of propylene and hexene
[0061] The polymerization process and reaction conditions were the same as in Example 14, but 31.6 mL of toluene and 18.4 mL of 1-hexene were added. Polymerization activity: 52500 kg·mol -1 (Hf) h -1 , polymer Mw = 4730 kg·mol -1 , Mw / Mn=2.0, T g =-14°C, tensile stress: 1.5MPa, elongation at break>2000%, 1-hexene content in the copolymer 17.4mol%.
[0062] Example 18: Copolymerization of propylene and decene
[0063] The polymerization process and reaction conditions were the same as in Example 14, but 31.6 mL of toluene and 18.4 mL of 1-hexene were added. Polymerization activity: 22500 kg·mol -1 (Hf) h -1 , polymer Mw = 3730 kg·mol -1 , Mw / Mn=2.0, T g =-18℃, tensile stress: 1.3MPa, elongation at break>2000%, content of 1-decene in the copolymer is 13.2mol%.
[0064] Example 19: Copolymerization of propylene and ethylene
[0065] The polymerization reaction was carried out on a 1L high-pressure steel autoclave homogeneous solution evaluation device. After the reactor was fully replaced with high-purity nitrogen, 200mL of toluene was injected with a syringe, the contents of the reactor were heated to 120°C, and the reactor was saturated with 1MPa propylene. 2μmol of catalyst, 100μmol of methylaluminoxane, and 2.2μmol of triphenyl carbon tetrakis (pentafluorophenyl) borate were added to the glove box, dissolved with toluene and transferred to the catalyst storage tube through a syringe, and then pressed into the reactor with nitrogen (over 1MPa). During the polymerization process, the reaction pressure was ensured to be 1MPa by continuously introducing propylene gas. At this time, the propylene pressure was maintained at a certain pressure, and ethylene was directly introduced into the reactor so that its amount based on propylene was 3.5wt%, and the reaction was carried out at a constant temperature for 10min. 2mL of ethanol was pressed into the reactor under nitrogen (over 1MPa), and the reactor was cooled and exhausted. The substance in the reactor was poured into a large amount of ethanol, and the polymer precipitated. The polymer was filtered to obtain the polymer, washed with a small amount of ethanol, and finally vacuum dried overnight and weighed. Polymerization activity: 32500kg·mol -1 (Hf) h -1 , polymer Mw = 1730 kg·mol -1 , Mw / Mn=2.0, T g =-15℃, tensile stress: 2.3MPa, elongation at break>2000%, ethylene content in the copolymer 48.3wt%.
[0066] Example 20: Copolymerization of propylene and ethylene
[0067] The polymerization process and reaction conditions were the same as in Example 19, except that the input amount of ethylene was changed to 2.0 wt% based on the input amount of propylene. Polymerization activity: 29500 kg·mol -1 (Hf) h -1 , polymer Mw = 2250 kg·mol -1 , Mw / Mn=2.1, T g =-13℃, tensile stress: 1.8MPa, elongation at break>2000%, ethylene content in the copolymer 26.7wt%.
Claims
1. A method for preparing an ultra-high molecular weight propylene-based elastomer, wherein: The ultra-high molecular weight propylene-based elastomer is prepared by homopolymerization of propylene, copolymerization of propylene and ethylene, and copolymerization of propylene and α-olefin; the catalyst used is a quinoline amine-based binuclear metal hafnium catalyst; the co-catalyst used is one or more of tris-pentafluorophenyl boron, triphenylcarbonium tetrakis(pentafluorophenyl) borate, aluminoxane, alkyl aluminum, and alkyl aluminum chloride; the molecular weight of the propylene-based elastomer is 50 to 500×10 4 g / mol, molecular weight distribution is 1.1-4.0, isotacticity (measured as the percentage of isotactic sequence pentads [mmmm] of propylene units in propylene molecular chains) is 10-50%, glass transition temperature is -50-0°C, tensile strength is 0.1-15MPa, elongation at break is 100-3000%, and it has excellent mechanical properties.
2. The method for preparing an ultra-high molecular weight propylene-based elastomer according to claim 1, characterized in that: The quinolineamino binuclear metal hafnium catalyst has a structure as shown in formula (I):
3. The method for preparing an ultra-high molecular weight propylene-based elastomer according to claim 1, characterized in that: The α-olefin is one or more of 1-butene, 1-hexene, 1-octene and 1-decene.
4. The method for preparing an ultra-high molecular weight propylene-based elastomer according to claim 1, characterized in that: The aluminoxane is methylaluminoxane, ethylaluminoxane or isobutylaluminoxane; the alkylaluminum is trimethylaluminum, triethylaluminum, triisobutylaluminum or tri-n-hexylaluminum; and the alkylaluminum chloride is diethylaluminum monochloride, diethylaluminum sesquichloride or ethylaluminum dichloride.
5. The method for preparing an ultra-high molecular weight propylene-based elastomer according to claim 1, characterized in that: The polymerization temperature is 0-180° C., the polymerization pressure is 0.1-4 MPa, the molar ratio of the catalyst to the co-catalyst is 1:(1-5000), the reaction time is 0.1-24 hours, and the polymerization solvent is one or more of n-hexane, n-heptane, n-pentane, and toluene.
Citation Information
Patent Citations
Process for preparing atactic polypropylene catalyst
CN1262283A